Strong and Fatigue‐Resistant Hydrogels via Poor Solvent Evaporation Assisted Hot‐Stretching for Tendon Repair - Huamin Li; Ying Zhang; Haidi Wu; Zhanqi Liu; Cheng Guan; Jin Zhang; Jingyi Chen; Shaohua He; Xuewu Huang; Wancheng Gu; Yiu Wing Mai; Jiefeng Gao (Advanced Science, 2025)
Abstract It is highly desirable but still remains challenging to develop high‐performance hydrogels with satisfactory mechanical properties for tissue engineering. Here, anisotropic yet transparent hydrogels (AHs) are prepared for tendon repair via a facile “poor solvent evaporation assisted hot‐stretching” strategy. AHs have great mechanical properties with tensile strength, toughness, and fracture energy as high as 33.14 ± 2.05 MPa, 44.1 ± 3.5 MJ m−3, and 106.18 ± 7.2 kJ m−2, respectively. Especially, AHs show unique flaw‐insensitive characteristics, and cracks can only deflect along the fiber alignment direction rather than propagate transverse to this direction, showing an interesting self‐protection function. The high strength, toughness, and fatigue resistance originate from the hierarchal structure of AHs, i.e., the densified polymeric network comprising fiber bundles and nanofibrils with aligned macromolecular chains, crystalline domains, and intermolecular hydrogen bonds. AHs with superior biocompatibility and swelling resistance can be used to repair rat tendons, and implantation of AHs can promote collagen regeneration for the tendon repair. This study provides a new method to fabricate strong and anti‐fatigue hydrogels as a new class of promising materials for soft tissues.